Do It Yourself Travel as a Gen Z Travel Culture in the Digital Era in Indonesia - Rahmaini, Indah Sari; Hanandini, Dwiyanti; Pramono, Wahyu; Malik, Rifki Maulana Iqbal (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2025)
This study aims to examine how the practice of DIY travel using the Do It Yourself (DIY) concept was popularized by Ulrich Beck in the late-modern era. This research uses a qualitative approach. The data collection technique was an in-depth interview with Spradley’s data analysis. The research informants were taken using purposive techniques. The study results show three practices of Gen Z carrying out DIY travel culture. First, the DIY travel culture is an act of resistance to consumerism and capitalism. Second, DIY travel culture creates a biographical trajectory. Third, to find value on the journey. This study has methodological limitations because it is researched using Ulrich Beck's theory of DIY and reflexive society, social class variables are ignored in this study and only categorize the group of young people who like to travel as the creation of their trips without being based on economic orientation